Interdisciplinary Considerations for Diagnosing Aphasia in the Schizoaffective Patient: A Case Report - Warner, Heather; Cometz, Alexa (International journal of language & communication disorders, 2023)
Background: Patients with schizophrenia present with both cognitive impairment as well as language difficulties. There are similarities in the language output of patients with schizophrenia and patients with aphasia, thus a differential diagnosis of patients who present with a question of dual diagnoses can be a clinical challenge. This case report highlights the importance of an interdisciplinary approach to a patient with schizophrenia who benefitted from intervention from both psychiatry and speech--language pathology services due to the patient's unique verbal output. Aims: The primary aim of this case report is to highlight the critical importance of interdisciplinary collaboration in this patient population. The secondary aim is to disseminate an interesting and unique clinical phenomenon whereby the patient demonstrated an awareness of two distinct speech patterns and the unique ability to 'code switch' between them, something not commonly appreciated in this clinical population. Methods & Procedures: This case report describes a patient seen as part of routine clinical care. Information shared was solely observational and involved dissemination of information regarding case history, assessment and treatment plan. No interventions were implemented as a part of this study. Outcomes & Results: Interprofessional communication was critical in order to diagnose a patient with schizophrenia with an atypical speech pattern. The patient's language output did not manifest as a true aphasia but rather as two distinct language patterns that the patient could use at will. This ability to 'code switch' between languages is a unique clinical profile that is atypical of patients with schizophrenia.